Új kihívások a középszintű államigazgatásban 2016-tól napjainkig A területi kormányhivatalok és járások továbbfejlesztésének főbb lépései és iránya - Barta, Attila; Jakab, Viktória (Debreceni Jogi Műhely, 2017)
This paper deals with the alteration of sub-national representation of government. Nowadays in Hungary the aforementioned institutions are called county (capital) government offices. The overview gives rise to the following research questions: Who are these representatives and what is the role of territorial government offices? Why interesting the Hungarian administrative improvement? What the future holds? The study concludes that the Hungarian Government has a comprehensive plan on the development of public administration until 2020, and the government offices and their districts play a pivotal role in this plan.